THE CASE FOR AN INTEGRATED EFFORT BY SCHOOLS IN ORDER TO PROMOTE EQUITY AND HARMONY AMONG DIFFERENT SOCIAL GROUPS IN THE NEW MILLENIUM IN SRI LANKA - Rupasinghe, S (My University, 2012)
The objective of this paper is to discuss the need to develop school to school linkages, possibly in the form of school clusters, in order to bring different socio-economic, religious and ethnic groups close together for the purpose of promoting equity and national harmony in the new millenium. In the first section of the paper under the sub title – the legacy of colonial education, the devisive and disintegrating trends in the school system during successive colonial regimes, mainly the British, have been discussed. In the section immediately following, attempts made towards the setting up of a national system of education on the eve of independence in 1947, and, in the post independence era have been described. In the third section attention has been paid to the negative aspects of the present school system which hinder national integration. In the final section the benefits, feasibility and the urgent need for school to school linkages in the form of clusters have been argued with the fervent hope of forging ahead for a united Sri Lanka.